PODPORZĄDKOWANIE TELEPRACOWNIKA W STOSUNKU PRACY - Duchna, Sylwia; Paluszkiewicz, Magdalena (Zeszyty Prawnicze, 2016)
THE SUBORDINATION OF THE TELEWORKER IN THE EMPLOYMENT RELATIONSHIP Summary The aim of this article is to characterise the relation of subordination of teleworkers. The continuous development of various flexible forms of employment such as teleworking is affecting the traditional concept of subordination in the employer-employee relationship. In teleworking subordination is modified with regards to the workplace, which is located outside the employer’s domain. To supervise his teleworking employees the employer has to communicate with them over a certain distance. Hence, in the authors’ opinion, teleworking is characterised by certain specific features. An employer considering teleworking as a potential form of employment should take these special features into account alongside the qualifications of his prospective employeesbefore he decides to adopt teleworking.